2018
DOI: 10.1002/term.2625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the three‐dimensional culture of human bone marrow mesenchymal stromal cells within a macroporous polysaccharides scaffold on Pannexin 1 and Pannexin 3

Abstract: Because cell interactions play a fundamental role for cell differentiation, we investigated the expression of Pannexin 1 and Pannexin 3 in human bone marrow mesenchymal stromal cells (HBMSCs) in a three-dimensional (3D) microenvironment provided by a polysaccharide-based macroporous scaffold. The pannexin (Panx) family consists of three members, Panx1, Panx2, and Panx3. The roles of Panx large-pore ion and metabolite channels are recognized in many physiological and pathophysiological scenarios, but the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A homogenous seeding of MC3T3-E1 cells within the pore network was achieved by the simple addition of a cell suspension on freeze-dried scaffolds. Isolated cells of different origins (species, tissues), two or more cell types, or cell clusters can be accommodated in these 3D porous scaffolds [17][18][19]21]. Such scaffolds are suitable for cell culture in 3D (especially when cell clustering and spheroid growth is necessary for studying cell development and differentiation), for tissue engineering or for pharmacological assays in 3D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A homogenous seeding of MC3T3-E1 cells within the pore network was achieved by the simple addition of a cell suspension on freeze-dried scaffolds. Isolated cells of different origins (species, tissues), two or more cell types, or cell clusters can be accommodated in these 3D porous scaffolds [17][18][19]21]. Such scaffolds are suitable for cell culture in 3D (especially when cell clustering and spheroid growth is necessary for studying cell development and differentiation), for tissue engineering or for pharmacological assays in 3D.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we address the mechanisms of pore formation by freeze-drying in a polysaccharide-based hydrogel scaffold designed for bone tissue engineering [16]. This biomaterial is under research and industrial developments [17][18][19][20][21]. The scaffolds are manufactured according to Route 1 with a low cooling rate.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides that mimic regulatory sequences of pannexins have been widely considered as a selective means to block PANX1 channels [69]. The best known of these is 10 PANX1, which is considered a specific blocker of PANX1 and is widely used in both cell and organoid cultures [70]. With the recent arrival of high-resolution structural knowledge of PANX1 channels in different activation states, it should now be possible to creatively design and synthesize strategic peptides that best regulate PANX1 channels [71][72][73][74].…”
Section: Clinically Deployed Drugs Targeting Pannexins That May Have Utility In Cancer Treatmentsmentioning
confidence: 99%
“…The upregulation of some osteoblastic genes in VKAIV-containing hydrogels can be explained by the cellular organization as spheroids. Our group has already shown that spheroid organization can provide numerous cellular contacts, stimulating junctional proteins such as connexin 43 or pannexins that could drive the osteogenic differentiation of MSCs [57,58].…”
Section: In Vivo Evaluationmentioning
confidence: 99%